THE CORRELATION OF PARENTING STYLE WITH UNDERGRADUATE MEDICAL STUDENTS’ ACADEMIC INTEGRITY IN A MEDICAL SCHOOL - Puspa Maharani; Hikmah Muktamiroh; Lasma Nurhayati (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Academic integrity is one of the main principle in academic culture. Academic integrity, defined as obedience to the principle in academic sphere. However, violation to the academic principle is a common phenomenon occurred in the high education. Integrated academic is closely related to morality, while morality is highly influenced by the parenting method. This study aimed to find relationship between parenting method and academic integrity behavior of student in academic stage of Medical Faculty.Method: This study conducted using proportional stratified random sampling with total sample of 225 medical students, the data from this study was collected from the questionnaire. The design was cross sectional method. Data was analyzed using Chi-Square test. Results: From Chi-Square test, the result for P Value was P=0.011, which means it was below P < 0,05. Conclusion: We can conclude that there is meaningful correlation between parenting method with academic integrity behavior of student in academic stage of Medical Faculty.